Beginning & intermediate algebra - Hendricks, Andrea (McGraw Hill, 2013)
Beginning and Intermediate Algebra and its supplemental materials coupled with ALEKS or Connect Math Hosted by ALEKS allow for both fulltime and parttime instructors to teach more than just the math in any teaching environment without an overwhelming amount of preparation time or even classroom time.